Voice in Adversity: The Impact of Bullying on Victims' Mental Health (Case Study at SMK PGRI 2 Malang) - Salsabilla, Amelia Eka; Andriany, Ayu Viryavasthi Talitha; Parahita, Senja Putri; Apriani, Rizka; Sintiawan, Naya (Proceedings Series of Educational Studies, 2024)
Basic education is a place where individuals build knowledge, attitudes, and positive behaviors that are used for future life. However, in reality, there have been many practices that are not for basic education, such as bullying in the school environment. This research aims to reveal the impact of bullying on the mental health of victims who are students of SMK PGRI 2 Malang. This study uses a qualitative case study method involving three students who are victims of bullying as the main informants. Informants were taken through purposive sampling techniques. Data were collected through structured interviews, observations, and document analysis. The collected data was analyzed using the Miles and Huberman model which consisted of data reduction, data presentation, and conclusion drawn. The process of data validity in this study uses the source triangulation technique. The results of the study showed that bullying had a significant impact on the mental health of the victim, such as anxiety, decreased self-confidence, social exclusion, and prolonged feelings of insecurity. In addition, victims tend to normalize the bullying they experience and are reluctant to report it to the school, especially BK teachers because of a lack of trust in the teacher's abilities and responses. This research highlights the importance of the role of BK teachers in handling bullying cases at school as well as fostering positive relationships and supporting students. Keywords: Bullying; Mental Health; Vocational School Students